The Factors that Influence Income Level in Small Medium Enterprise (case study in Tempe Chips Industry Sanan Malang) - Hattantyo, Febby Satya (Jurnal Ilmiah Mahasiswa FEB, 2016)
Unique industry food in Malang city especially one of small industry was develop. This Industry can create job field and also absorb labor in massive, then can create income for society and region. From all various type of special food from Malang, Tempe chips industry is one of industry which has some potentials to be developed as souvenirs for all tourists that come to Malang city. From this phenomena the writer tries to do a research about the impact of capital, production, length of business, and labor variables to income level. Because the increase of income in business or industry is a main enforcement element for industry to keep surviving and developing. The purposes of this research are: (1) to know the impact of capital, production, long of business, and labor to income of the Tempe chips producers in Sanan area of Malang city; (2) to know which factor that have more influence in the income level of Tempe chips industry in Sanan area of Malang city. The collection of the data comes from primary and secondary data sources. Primary data is in questioner form and secondary data is a data from Department of Industry and Trade. The respondents are the owner of each Tempe chips business which are 20 industry in number. The sampling technique that is used in this research is by saturation sampling method (census), by taking all members of sample. Based on the result of multiple linear regression calculation by using statistic program SPSS, is gotten a multiple linear regression equation below: Y = -69,235 + 0,672X1 + 0,085X2+ 1,421X3+ 7,130X4+ e. the result of data analysis is there are 3 independent variables (capital, production, and labor) that have a positive and significant relationship with the income of Tempe chips producers in Sanan, Malang city. The variable which has no impact is length of business. The variable that has a dominant impact to the income of Tempe chips producers in Sanan, Malang city, is labor. Key word: Small Medium Enterprise, Income, capital, Production, Labor, Length of Business